Women and the Word - King, J. author. aut Link
X, 207 p.
Keywords: Women and the Word examines why, in today's secular society, so many of the finest British and American women novelists seem preoccupied with Biblical themes and stories. It offers informed and challenging analysis of individual novels and stories for the literary critic and student. By analysing those texts in the context of myth and religion, however, it also makes an important and ground-breaking contribution to a number of the inter-disciplinary debates taking place within women's studies.